(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
By studying the surface morphology and crystal orientation of the Zn-0.5Sn coating, it guides improving the surface performance of the hot-dip galvanizing coating. Scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) were used to analyze the typical morphology and element distribution of spangles. The surface texture of the coating was analyzed by X-ray diffraction (XRD). Electron backscatter diffraction (EBSD) was used to analyze the crystal orientation of spangles. The results show that Sn segregates among the spangle dendrites, and the tin-rich phase exists in the form of a metastable divorced eutectic structure. The components of the tin-rich phase are similar. The crystal orientation of spangle affects the morphology of spangle, leading to the formation of feathery, ridged, and orthogonal dendrite arm spangle. When the angle between the <0001> orientation of the spangle crystal and the normal of the steel base surface changes from 0° to 90°, the spangle morphology evolves from feathery to orthogonal dendrite arm. The misorientation within a spangle is small while between spangles is quite large. The misorientation along the direction of the dendrite arm is relatively smooth and slow, while perpendicular to the direction of the dendrite arm presents a jumping and irregular fluctuation.